2010
DOI: 10.1111/j.1552-3934.2010.00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Adequate Emergency Funds Including the Effects of Seeking Professional Advice and Industry Affiliation

Abstract: This research examined the effects of seeking professional financial advice and being employed in different industries on a household’s likelihood of holding adequate emergency funds to cover six or more months without income. The theory of precautionary savings provided a conceptual framework for the study. Three measures of emergency funds were analyzed: Subjective funds, Quick funds, and Comprehensive funds. The sample consisted of working household heads in the 2007 Survey of Consumer Finances. Seeking pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Blue‐collar workers were more likely to be saving or to have already saved than to be not saving for medium‐term expenses. Anong and DeVaney () found that white‐collar workers were more likely to state adequate levels of precautionary savings. In another study, DeVaney and Anong () found that blue‐collar workers were less likely to have employer‐sponsored health insurance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blue‐collar workers were more likely to be saving or to have already saved than to be not saving for medium‐term expenses. Anong and DeVaney () found that white‐collar workers were more likely to state adequate levels of precautionary savings. In another study, DeVaney and Anong () found that blue‐collar workers were less likely to have employer‐sponsored health insurance.…”
Section: Discussionmentioning
confidence: 99%
“…Anong and DeVaney () found that those in white‐collar industries such as finance, real estate, and advertising were not only more likely to state adequate amounts needed in emergency savings but they were also more likely to have adequate levels of emergency savings. It was expected that older respondents, married couples with no dependent children, men, White people, and white‐collar workers would be more likely to be saving or to have already saved for their expected medium‐term expenses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, with one well-constructed table, Anong and DeVaney (2010) provide information about the independent and dependent variables used, how each of the variables is measured, and weighted estimates of the population parameters. As a reader, I appreciate authors who take me step by step through univariate descriptions of the sample, particularly when these descriptions are accompanied with relevant measurement information.…”
Section: Content Claritymentioning
confidence: 99%
“…As a reader, I appreciate authors who take me step by step through univariate descriptions of the sample, particularly when these descriptions are accompanied with relevant measurement information. For example, with one well-constructed table, Anong and DeVaney (2010) provide information about the independent and dependent variables used, how each of the variables is measured, and weighted estimates of the population parameters. Tables are efficient alternatives to lengthy text and can stand on their own when authors have provided the information necessary for readers to develop an understanding of the participants, constructs, and variables represented.…”
Section: Content Claritymentioning
confidence: 99%
“…Empirical studies used the life‐cycle stage as an important explanatory variable in spending behavior such as expenditure patterns (Putler, Li, & Liu, 2007; Wagner & Hanna, 1983; Wilkes, 1995), spending and home production (Hurst & Aguiar, 2004), child influence on family spending (Douthitt & Fedyk, 1988), and expenditures on food (Blanciforti, Green, & Lane, 1981), out‐of‐pocket healthcare (Hong & Kim, 2000), and tourism (Lawson, 1991). This variable is also used to examine its effects on borrowing and saving behaviors such as housing cost burden (DeVaney, Chiremba, & Vincent, 2004), ownership of financial assets (Xiao, 1996), determinants of adequate emergency funds (Anong & DeVaney, 2010); and debt holding (Baek & Hong, 2004; Yilmazer & DeVaney, 2005).…”
mentioning
confidence: 99%